Surface Activation of Calcium Bentonite by Acid Treatment - Suryakanta Parida; Achyut Kumar Panda (International Journal of Research in Chemistry and Environment (IJRCE), 2017)
Calcium bentonite was treated with sulphuric acid of 3M concentration by mechanical stirring and thermal refluxing condition followed by calcination at 500°C for 1h. The physico-chemical characteristics of acidleachedcalcium bentonite were studied by different instrumental analytical techniques. The effect of thermo-acidic treatment is more pronounced as compared to mechano-acidic treatment. XRFand FTIR studies indicate that acid treatment leads to the removal of the octahedralAl3+ and other cations. XRD of acid treated calcium bentoniteinfer that acid treatmentwith mechanical stirring and heating provoked anamorphization of crystalline clay. Theacid treatment increased the Si/Al ratio, surface area and water content. Solids thus obtainedby acid treatments can be used as promising adsorbents and catalyst supports for acid catalysed reactions.